SYNTHESIS MATERIAL OF ZEOLITE NANOPOROUS (ZSM-5) FROM COAL FLY ASH - Bambang Sunendar Purwasasmita; Agung Kurnia; Arie Wibowo (Institut Teknologi Bandung, 2010)
Coal fly ash (CFA) is the waste of coal usage that requires serious attention on handling because it is have the large quantity and containing a dangerous substances for environmental. The interesting method of waste processing of CFA is using CFA as zeolite raw material because CFA have a rich silicate and alumina. In this study, CFA is used as a raw material for zeolite synthesis nanoporous (ZSM-5) so that expected could be a solution for waste processing of CFA and also could be deliver a valuable materials that needed on many applications. Based on the result of characterization XRD and SEM, was known that structure of ZSM-5 and other zeolites (Na12Al12Si12O48.27H2O and Na0,3Al2,564Si100O203,996) have been successfully synthesized on hydrothermal processing at temperature of 97°C and the pressure of 1,3 bar.